Strengthening the Role of the State Language as a Unifying Factor of Interethnic Harmony : The Case of the Republic of Uzbekistan - Qurbonova Marguba (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This study aims to investigate the role of the state language in fostering interethnic harmony and social cohesion in a multilingual society. The research focuses on language policy implementation, linguistic integration, and the relationship between language use and civic unity. A qualitative analytical method was employed through policy analysis, sociolinguistic literature review, and examination of national language regulations. The findings demonstrate that the promotion of the state language strengthens national identity and facilitates social integration while maintaining respect for linguistic diversity. Nevertheless, challenges related to unequal language proficiency and minority inclusion persist. The study concludes that balanced language policies integrating state language development with multicultural principles are crucial for sustaining interethnic harmony.